Oxidized collagen stimulates proliferation of vascular smooth muscle cells - Bacáková, L; Wilhelm, J; Herget, J; Novotná, J; Eckhart, A (Experimental and molecular pathology, 1997)
We hypothesize that the vascular smooth muscle proliferation after lung injury results from oxidative damage to the matrix proteins in the walls of pulmonary blood vessels. The smooth muscle cells (SMC) isolated from rat aorta were cultured on the surface coated with oxidized and nonoxidized (control) collagen of type I. Oxidation of collagen was induced by UV irradiation and characterized by fluorescence tridimensional spectral arrays and by gel electrophoresis. From day 1 to 6 of the experiment, SMC proliferated more rapidly on the oxidized collagen than on the control surface. At high SMC population densities (day 9 of experiment) the difference disappeared. After 10 min of trypsinization the cells growing on oxidized collagen rounded and detached completely from the growth surface. The control cells on nonoxidized collagen detached only after 30 min of trypsinization. We conclude that oxidation of collagen of vascular wall matrix may participate in stimulation of SMC proliferation after oxidant tissue injury.
Keywords: buněčné dělení; Animals; trypsin; potkani inbrední WKY; Collagen; Muscle, Smooth, Vascular; buněčná adheze; kolagen; Cell Adhesion; kultivované buňky; Rats, Inbred WKY; oxidace-redukce; Cells, Cultured; Male; Oxidation-Reduction; svaly hladké cévní; krysa rodu Rattus; Trypsin; zvířata; mužské pohlaví; Cell Division; Rats